Neuroplastic effects of transcranial direct current stimulation on painful symptoms reduction in chronic Hepatitis C: a phase II randomized, double blind, sham controlled trial - Aline Patricia Brietzke; Joanna Ripoll Rozisky; Jairo Alberto Dussan-Sarria; Alícia eDeitos; Gabriela eLaste; Priscila Fortes Thomas Hoppe; Suzana eMuller; Iraci Lucena da Silva Torres; Mario Reis Alvares-da-Silva; Rivadavio eAmorim; Felipe eFregni; WOLNEI eCAUMO (Frontiers in Neuroscience, 2016)
Introduction: Pegylated Interferon Alpha (Peg-IFN) in combination with other drugs is the standard treatment for chronic hepatitis C infection (HCV) and is related to severe painful symptoms. The aim of this study was access the efficacy of transcranial direct current stimulation (tDCS) in controlling the painful symptoms related to Peg-IFN side effects. Material and Methods: In this phase II double-blind trial, twenty eight (n=28) HCV subjects were randomized to receive either five consecutive days of active tDCS (n=14) or sham (n=14) during five consecutive days with anodal stimulation over the primary motor cortex region using 2 mA for 20 minutes. The primary outcomes were visual analogue scale (VAS) pain and brain-derived neurotrophic factor (BDNF) serum levels. Secondary outcomes were the pressure-pain threshold (PPT), the Brazilian Profile of Chronic Pain: Screen (B-PCP:S) and drug analgesics use. Results: tDCS reduced the VAS scores (P<0.003), with a mean pain drop of 56% (p<0.001). Furthermore, tDCS was able to enhance BDNF levels (p<0.01). The mean increase was 37.48% in the active group. Finally, tDCS raised PPT (p<0.001) and reduced the B-PCP:S scores and analgesic use (p<0.05). Conclusions: Five sessions of tDCS were effective in reducing the painful symptoms in HCV patients undergoing Peg-IFN treatment. These findings support the efficacy of tDCS as a promising therapeutic tool to improve the tolerance of the side effects related to the use of Peg-IFN. Future larger studies (phase III and IV trials) are needed to confirm the clinical use of the therapeutic effects of tDCS in such condition. Trial registration: Brazilian Human Health Regulator for Research with the approval number CAAE 07802012.0.0000.5327